Guidelines for Holter and Wearable Electrocardiogram Monitoring in Arrhythmia Diagnosis and the Role of Medical Technologists - Do-Hee KIM; Ji-Yeon CHANG (Korean Journal of Clinical Laboratory Science)
Cardiovascular disease ranks as the second leading cause of mortality after cancer, with arrhythmias, a significant subset, showing a marked annual increase in prevalence. Atrial fibrillation, often asymptomatic, necessitates early diagnostic testing. Long-term monitoring through Holter and wearable electrocardiogram (ECG) devices enhances the detection rates. Holter monitoring allows 24- or 48-hour continuous ECG recording but is limited by patient discomfort and device bulk. Wearable devices enhance patient compliance and enable extended monitoring periods, but limitations in AI-based analysis persist. This paper highlights the critical roles and responsibilities of medical technologists in Holter and wearable ECG monitoring, assessing their strengths and considerations for clinical applications. The results underscore the need to enhance technologists’ skills to ensure accurate arrhythmia diagnoses and reduce procedural errors. Comprehensive guidelines on processes, such as essential processes, proper electrode placement, and accurate data transmission, offer practical recommendations for conventional ECG monitoring and data analysis.